Central retinal artery occlusion following cosmetic filler injection - Rojdamrongrantana, Duangmontree; Bawornwattanadilok, Paiboon; Muangsiri, Sirineen (Asian Medical Journal and Alternative Medicine, 2023)
A 37-year-old female presented to the clinic with a sudden right vision loss of her right eye following injecting filler in her dorsum nasal area. On exam, her vision was no perception of light at the first visit. Multiple doses of subcutaneous hyaluronidase was injected along her nasal prior to her arrival at Thammasart hospital. The management at Thammasart hospital was ocular massage, hyperbaric oxygen treatment, anterior chamber paracentesis and administration of aqueous suppressants. Despite cerebral angiography injection 1500 IU of hyaluronidase into orbital branch of middle meningeal artery, the patient had no light perception.